A composite current collector pole ear and its preparation method and application

By coating conductive metal paste on the foil of the composite fluid collector electrode, forming a conductive metal layer and welding the electrode, the problem of difficult welding of the composite fluid collector electrode electrode is solved, and the battery performance improvement and process simplification is achieved .

CN116826066BActive Publication Date: 2025-02-11SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310795482.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-02-11
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The welding of composite fluid collector ears is difficult, and traditional methods require complex process flow and high equipment requirements, resulting in poor battery performance and limited rate performance and cycle stability.

Method used

By coating conductive metal paste at the reserved welding electrode of the composite foil, a conductive metal layer is formed, and the electrode ears are welded on the conductive metal layer, so that the two surfaces of the composite fluid collector ear can conduct electricity at the same time, thus solving the conductivity Poor sex problem.

Benefits of technology

This method simplifies the welding process of composite fluid collector pole ears, reduces equipment and process complexity, improves the energy density and safety of the battery, and ensures the stability and efficiency of battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116826066B_ABST
    Figure CN116826066B_ABST
Patent Text Reader

Abstract

The present invention provides a composite current collector pole ear and a preparation method and application thereof. The composite current collector pole ear comprises a composite foil, a conductive metal layer and a pole ear. The conductive metal layer is coated on the edge of the composite foil reserved for welding pole ear and partially extends to the two side surfaces of the composite foil reserved for welding pole ear. The pole ear is arranged on the side of the conductive metal layer away from the composite foil. The present invention effectively improves the welding problem between the composite current collector and the pole ear, reduces the resistance at the pole ear welding point, and improves the cycle stability of the battery. The application of the composite current collector pole ear improves the energy density and safety of lithium-ion batteries without introducing other equipment and complex process flows, and effectively ensures the performance of the battery, which is conducive to the research and development of new batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite current collector pole ear and a preparation method and application thereof. Background Art

[0002] The current collector is one of the indispensable components of lithium-ion batteries. It not only needs to carry active materials, but also be able to collect and output the current generated by the active materials, which is beneficial to reduce the internal resistance of lithium-ion batteries, improve coulombic efficiency, cycle stability and rate performance.

[0003] The composite current collector is a composite material formed by depositing copper / aluminum conductive layers on both sides of the base film using polymer materials such as PP / PET / PI as the intermediate base film through processes such as coating. The structure is a "metal-polymer material-metal sandwich structure".

[0004] No matter how many layers of tabs there are in the traditional pure metal foil current collector, when welding the tabs, you only need to place the tabs close to one side of the reserved welding position of the current collector to achieve through-conduction of each layer. However, due to the "sandwich" structure of the composite current collector, the intermediate matrix is ​​a non-conductive polymer, and the conductivity in the vertical direction of the collector is very poor, almost insulating. The traditional single-piece tab can only be welded on one side of the current collector. Affected by the poor conductivity of the intermediate polymer matrix, the current conduction on the other side of the current collector will be affected. If it is a multi-layer current collector welding, due to the poor conductivity of the intermediate layer, it is basically not welded or welded. The farther the current collector is from the welding side of the tab, the greater the impact on its current conduction ability. This is not good for the rate performance of the battery and the consistency of the capacity of each internal layer, resulting in poor battery performance and accelerated attenuation. Therefore, the foil transfer or welding of the composite current collector is one of the core technologies of its application. The typical composite current collector welding process mainly includes foil folding and roll welding. The design of the folding mechanism of the foil folding method is very important for the connection between the composite current collector and the foil. Not only does it require special equipment, but the folding will also increase the welding thickness of the pole ear and increase the number of contact interfaces. As for the roll welding of the pole ear, the actual effect is not ideal, and the welding thickness is limited. The mainstream is still ultrasonic welding. If the foil is not folded, the two foils are welded up and down to avoid the problem of the foil needing to be folded. However, this method requires inserting metal foils above and below the composite current collector foil in advance, which will also increase the thickness and quality of the pole ear welding point and increase the difficulty of welding operation. In addition, there is also the application of avoiding the folding of the foil and the welding of two foils up and down by designing a forked pole ear, but the bifurcation of the pole ear will not only increase the manufacturing difficulty and cost of the pole ear, but the bifurcation of a single pole ear is always limited, and the application value is not high for multi-layer laminated batteries.

[0005] CN115425366A discloses a composite current collector pole ear welding structure and a welding method thereof, and the specific steps are: S1: connecting mutually offset pole ears on adjacent pole pieces respectively; S2: installing a plurality of connecting pieces on a connecting body respectively; S3: a gripping device moves the connecting body together with the connecting piece to above the pole piece, and the connecting piece is respectively inserted between adjacent pole piece pole ears, so that the pole piece pole ear and the connecting piece are superimposed on each other; S4: a first welding mechanism is arranged along the superposition direction of the pole piece pole ear and the connecting piece, a filling body is arranged on the connecting piece, and the first welding mechanism preheats and extrude-welds the pole piece pole ear; S5: ultrasonically welding the connecting piece to the pole piece pole ear through a second welding mechanism.

[0006] CN110936010A discloses a method for welding a composite current collector pole ear of a lithium battery. First, two metal pole ears are used to clamp the composite current collector pole ear, i.e., the pole ear of pole piece A, and pre-weld it once to form pole piece B; then pole piece B and pole piece A are stacked from bottom to top, and the pole ear of the composite current collector in pole piece B and the pole ear of the adjacent pole piece A are completely overlapped up and down, and the metal pole ears of all pole pieces B are completely overlapped up and down, and between adjacent pole pieces B and pole pieces A, the metal pole ear of pole piece B adjacent to pole piece A and the pole ear of adjacent pole piece A are pre-welded for a second time; finally, the multi-layer metal pole ear is finally welded to the positive pole ear or negative pole ear corresponding to the lithium battery.

[0007] The welding method of the composite current collector tab described in the above scheme is complex and has high requirements on equipment, is difficult to weld and will increase the thickness of the tab welding point. Summary of the invention

[0008] The purpose of the present invention is to provide a composite current collector pole ear and its preparation method and application. The present invention effectively improves the welding problem between the composite current collector and the metal pole ear, so that the application of the composite current collector pole ear can improve the energy density and safety of lithium-ion batteries without introducing other equipment and complex process flows, and effectively ensures the performance of the battery, which is conducive to the development and promotion of new batteries.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a composite current collector pole tab, comprising a composite foil, a conductive metal layer and a pole tab, wherein the conductive metal layer is coated on the edge of the composite foil reserved for welding the pole tab and partially extends to the two side surfaces of the composite foil reserved for welding the pole tab, and the pole tab is arranged on the side of the conductive metal layer away from the composite foil.

[0011] The present invention evenly arranges the conductive metal layer on the edge of the composite foil and slightly extends it to the surfaces on both sides of the current collector, and arranges the metal pole ear on the conductive metal layer, so that the two surfaces of the composite current collector pole ear can be conductive at the same time. The conductive metal layer arranged on the composite foil is thin and firmly bonded to the composite foil, and the conductive metal layer has good adhesion to the intermediate substrate of the current collector.

[0012] Preferably, the composite foil comprises an intermediate polymer layer and metal layers respectively arranged on both sides of the intermediate polymer layer.

[0013] Preferably, the intermediate polymer layer comprises any one of PET, PP or PI, or a combination of at least two of them.

[0014] Preferably, the metal layer independently includes any one of an aluminum layer, a copper layer, a stainless steel layer or a carbon-coated metal layer, or a combination of at least two of them, preferably a carbon-coated metal layer.

[0015] Preferably, the thickness of the carbon-coated layer of the carbon-coated metal layer is 0.8-1.2 μm, for example, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm.

[0016] Preferably, the thickness of the intermediate polymer layer is 5-8 μm, for example, 5 μm, 5.5 μm, 6 μm, 7 μm or 8 μm.

[0017] Preferably, the single layer thickness of the metal layer is 0.8-1.2 μm, for example, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm.

[0018] Preferably, the conductive metal layer extends to a width of 1 to 5 mm on a single side of the reserved welding tab foil, for example, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm.

[0019] Preferably, the thickness of the conductive metal layer is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0020] Preferably, the electrical conductivity of the conductive metal layer at room temperature is >10 mS / cm.

[0021] Preferably, the electrode tab comprises an aluminum electrode tab or a copper electrode tab.

[0022] In a second aspect, the present invention provides a method for preparing the composite current collector tab as described in the first aspect, the preparation method comprising the following steps:

[0023] (1) Take a composite foil and reserve foil for welding tabs at both ends and on the surface of the composite foil;

[0024] (2) Coating a conductive metal paste on the foil at the reserved welding tab, drying it, and welding the tab in a vertical direction at the location coated with the conductive metal paste to obtain the composite current collector tab.

[0025] For multi-layer stacked batteries, the reserved pole ears can be coated with conductive metal slurry in advance and the pole ears can be welded after drying. Alternatively, the composite current collector can be coated with active slurry to form pole sheets, the pole sheets can be stacked, the conductive metal slurry can be coated on the entire pole ear welding area and dried, and then the pole ears can be welded.

[0026] The method described in the present invention is highly compatible with the existing pole ear welding process, and there is no need to specially customize foil processing equipment, such as foil folding equipment, and there is no need to perform special processing on the existing pole ears. The pole ears do not need to be forked, and there is no need to use roll welding equipment. There is no need to lay foil on both sides of the composite current collector for welding. This method has little effect on the thickness and mass increase of the pole ear welding point, and is applicable to a wide range of occasions. It can effectively ensure the performance and stability of multi-layer laminated batteries using composite current collectors, improve the applicability of composite current collectors, and promote the application of lithium-ion batteries with both high energy density and high safety.

[0027] Preferably, the width of the foil reserved for the welding tab in step (1) is 1 to 2 cm, for example, 1 cm, 1.2 cm, 1.5 cm, 1.8 cm or 2 cm.

[0028] Preferably, the length of the foil reserved for the welding tab is 1.5 to 2.5 cm, for example, 1.5 cm, 1.8 cm, 2 cm, 2.2 cm or 2.5 cm.

[0029] Preferably, the conductive metal paste in step (2) includes any one of conductive silver paste, conductive aluminum paste, conductive platinum paste, conductive nickel paste, conductive copper paste, conductive tin paste or conductive gold paste, or a combination of at least two of them.

[0030] Preferably, the viscosity of the conductive metal paste is 150,000-200,000 cps, for example, 150,000 cps, 160,000 cps, 170,000 cps, 180,000 cps or 200,000 cps.

[0031] Preferably, the mass fraction of the conductive metal in the conductive metal paste is 80-90%, for example, 80%, 82%, 85%, 88% or 90%.

[0032] Preferably, the average particle size of the metal particles in the conductive metal paste is less than 100 nm.

[0033] Preferably, in step (2), the conductive metal paste extends on both sides of the foil material at the reserved welding tab in a direction parallel to the current collector to a width of 1 to 5 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm.

[0034] Preferably, the conductive metal paste is coated on both sides of the foil surface at the reserved welding lug, and the coating length from the top to the root of the lug along the direction perpendicular to the current collector is 50-100% of the lug length, for example: 50%, 60%, 70%, 80%, 90% or 100%.

[0035] Preferably, the coating method in step (2) includes spraying and / or scraping.

[0036] Preferably, the drying temperature is 80-120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C.

[0037] Preferably, the drying time is 6 to 24 hours, for example: 6 hours, 8 hours, 10 hours, 15 hours or 24 hours.

[0038] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the composite current collector tab as described in the first aspect.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present invention effectively improves the welding problem of the composite current collector tab, so that the application of the composite current collector tab improves the energy density and safety of lithium-ion batteries without the need to introduce other equipment and complex process flows, and effectively ensures the performance of the battery, which is conducive to the development and promotion of new batteries.

[0041] (2) The composite current collector tab of the present invention is made into a laminated battery, and the resistance between the aluminum tab and the 10th layer of composite foil tab can reach below 5.8Ω, which is very small compared to the resistance between the aluminum tab and the 1st layer of composite foil tab of 0.2Ω, and the retention rate of the prepared battery after 200 cycles of 1C charge and discharge can reach above 94.3%. Within the coating thickness range of the conductive metal layer selected by the present invention, the higher the conductivity of the conductive metal slurry, the more obvious the improvement of the welding resistance of the composite current collector tab, and the better the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic cross-sectional view of the composite current collector after coating the conductive metal layer as described in Example 1, wherein 101 is an aluminum layer, 102 is an aluminum layer, 103 is a PET layer, 104 is a conductive metal layer, and 105 is a conductive metal layer. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] Example 1

[0045] This embodiment provides a composite current collector electrode, and the preparation method of the composite current collector electrode is as follows:

[0046] (1) Take a carbon-coated aluminum-PET-aluminum composite foil, in which the PET is 6 μm thick, the aluminum layer and the carbon coating layer are 1 μm thick respectively, and the foil reserved for the welding tab is 1 cm wide and 2 cm long;

[0047] (2) At the reserved tab welding foil, a conductive silver paste is coated along the interface and surface, wherein the viscosity of the conductive silver paste is 180000 cps, the mass fraction of conductive silver in the conductive silver paste is 85%, the average particle size of the silver particles is <100 nm, the width of the coating parallel to the current collector direction on the reserved tab welding foil is 3 mm, and the length of the coating from the top of the tab downward in the direction perpendicular to the current collector is 1 cm, and then dried at 100° C. for 12 h, wherein the thickness of the conductive silver paste after drying (i.e., the thickness of the conductive metal layer) is 2 μm, and the average conductivity is 5*10 4 mS / cm, the cross-sectional schematic diagram of the composite current collector after coating with a conductive metal layer is shown in Figure 1 As shown, 101 is a carbon-coated aluminum layer, 102 is an aluminum layer, 103 is a PET layer, 104 and 105 are conductive metal layers arranged at both ends and part of the surface of the composite current collector, respectively, and aluminum tabs are welded in a vertical direction at the places coated with conductive metal paste to obtain the composite current collector tabs.

[0048] Example 2

[0049] This embodiment provides a composite current collector electrode, and the preparation method of the composite current collector electrode is as follows:

[0050] (1) Take a carbon-coated aluminum-PET-aluminum composite foil, in which the PET is 5 μm thick, the aluminum layer and the carbon coating layer are 0.8 μm thick respectively, and the foil reserved for the welding tab is 1 cm wide and 1.5 cm long;

[0051] (2) At the reserved tab welding foil, a conductive platinum paste is coated along the interface and surface, wherein the viscosity of the conductive platinum paste is 180000 cps, the mass fraction of conductive platinum in the conductive platinum paste is 80%, the average particle size of platinum particles is <100 nm, the width of the coating parallel to the current collector direction on the reserved tab welding foil is 1 mm, and the length of the coating from the top of the tab downward in the direction perpendicular to the current collector is 1 cm, and then dried at 80°C for 24 hours, wherein the thickness of the conductive platinum paste after drying is 1 μm, and the average conductivity is 3.1*10 4 mS / cm, and weld the aluminum electrode in the vertical direction where the conductive metal paste is coated to obtain the composite current collector electrode.

[0052] Example 3

[0053] This embodiment provides a composite current collector electrode, and the preparation method of the composite current collector electrode is as follows:

[0054] (1) Take a carbon-coated aluminum-PET-aluminum composite foil, in which the PET is 8 μm thick, the aluminum layer and the carbon coating layer are 1.2 μm thick respectively, and the foil reserved for the welding tab is 2 cm wide and 2.5 cm long;

[0055] (2) At the reserved tab welding foil, a conductive aluminum paste is coated along the interface and surface, wherein the viscosity of the conductive aluminum paste is 200000 cps, the mass fraction of conductive aluminum in the conductive aluminum paste is 90%, the average particle size of aluminum particles is <100 nm, the width of the coating parallel to the current collector direction on the reserved tab welding foil is 5 mm, and the length of the coating perpendicular to the current collector from the top of the tab downward is 1.3 cm, and then dried at 120° C. for 6 hours, wherein the thickness of the conductive aluminum paste after drying is 5 μm, and the average conductivity is 2*10 4 mS / cm, and weld the aluminum electrode in the vertical direction where the conductive metal paste is coated to obtain the composite current collector electrode.

[0056] Example 4

[0057] The only difference between this embodiment and embodiment 1 is that the thickness of the conductive silver paste after drying is 0.5 μm, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0058] Example 5

[0059] The only difference between this embodiment and embodiment 1 is that the thickness of the conductive silver paste after drying is 6 μm, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0060] Example 6

[0061] The only difference between this embodiment and the first embodiment is that the width of the conductive silver paste coated on the foil is 0.5 mm, and the other conditions and parameters are exactly the same as those in the first embodiment.

[0062] Example 7

[0063] The only difference between this embodiment and the first embodiment is that the width of the conductive silver paste coated on the foil is 6 mm, and the other conditions and parameters are exactly the same as those in the first embodiment.

[0064] Comparative Example 1

[0065] The only difference between this comparative example and Example 1 is that no conductive silver paste is applied, and other conditions and parameters are exactly the same as those in Example 1.

[0066] Performance Testing:

[0067] According to the type of composite current collector pole ear used in Examples 1-7, the same positive electrode active layer is coated thereon to prepare a positive electrode sheet, and the reserved pole ear size, conductive metal layer type, coating area and thickness, and drying method of Examples 1-7 are used to complete the processing of the composite current collector pole ear, and then laminated with the graphite negative electrode and the diaphragm, the number of positive electrode layers is 10, and the aluminum pole ear is welded in the vertical direction of the reserved pole ear conductive metal layer of the positive electrode sheet, and the subsequent assembly steps are completed. The prepared soft-pack battery has a design capacity of 5Ah. Comparative Example 1 is based on the pole sheet prepared in Example 1, and the reserved composite foil pole ear is not coated with a conductive metal layer, and the aluminum pole ear is directly welded on the composite foil pole ear. The rest is consistent with Example 1; the above battery uses a multimeter to test the resistance of the first layer of the foil at the welding point and the 10th layer of the composite aluminum foil below the front end of the pole ear (indicating the level of welding improvement), and the results of the battery cycle test are shown in Table 1:

[0068] Table 1

[0069]

[0070]

[0071] As can be seen from Table 1, from Examples 1-3, the composite current collector tab of the present invention is made into a laminated battery, and the resistance of the aluminum tab and the 10th layer of composite foil tab can reach 5.8Ω or less, which is very small compared to the 0.2Ω resistance of the aluminum tab and the 1st layer of composite foil tab, and the retention rate of the prepared battery 1C charge and discharge cycle 200 cycles can reach more than 94.3%. Within the coating thickness range of the conductive metal layer selected by the present invention, the higher the conductivity of the conductive metal slurry, the more obvious the improvement of the welding resistance of the composite current collector tab, and the better the cycle performance of the battery.

[0072] By comparing Example 1 with Examples 4-5, it can be seen that the thickness of the conductive metal layer at the reserved tab welding foil of the composite current collector of the present invention will affect its performance. When the thickness of the conductive metal layer is controlled at 1 to 5 μm, the performance of the composite current collector tab is better. If the thickness of the conductive metal layer is too high, it will not only increase the mass of the tab, affect the energy density, and increase the cost, but also increase the resistance between the tab layers, which is not conducive to battery circulation. If the thickness of the conductive metal layer is too small, the polymer layer in the composite current collector layer will penetrate the conductive coating due to ultrasonic extrusion during the welding process, causing the tab resistance to increase, which is also not conducive to battery circulation.

[0073] By comparing Example 1 with Examples 6-7, it can be seen that the extension width of the conductive metal layer at the reserved pole ear welding foil of the composite current collector of the present invention will affect its performance. The extension width of the conductive metal layer is controlled to be 1-5 mm, and the performance of the composite current collector is better. If the extension width of the conductive metal layer is too high, the amount of conductive metal slurry used will increase, which will not only increase the quality and cost of the battery core, but also because some pole ears are designed to be narrow, the conductive coating layers that extend too wide on both sides will be staggered, resulting in uneven coating thickness on the surface of the pole ear foil, inconsistent conductivity, increased resistance, and uneven force at uneven places during ultrasonic welding, which may tear the current collector; if the extension width of the conductive metal layer is too small, when welding the pole ear, the impedance may increase due to incomplete contact between the pole ear and the conductive metal coating, all of which are not conducive to the battery cycle stability.

[0074] Take a 10μm pure aluminum foil, coat both sides with a 1μm carbon layer, and cut it into a size of 1cm*2cm for the reserved tab of the composite current collector in Example 1. Take 10 pieces of carbon-coated aluminum foil of this size and weld them with the aluminum tab to form a tab + 10-layer foil structure. Use a multimeter to test the resistance of the first layer of foil at the front end of the tab and the welding point and the 10th layer of composite aluminum foil below. The resistances are 0.2Ω and 0.25Ω respectively, compared with the corresponding resistances of 0.5Ω and 530Ω in Comparative Example 1. The present invention significantly reduces the resistance between the reserved tab layers of the composite current collector and the welding point with the metal tab in the multi-layer laminated battery, and improves the cycle performance of the battery.

[0075] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite current collector electrode, characterized in that: The composite current collector tab comprises a composite foil, a conductive metal layer and a tab, wherein the conductive metal layer is coated on the edge of the composite foil reserved for welding tabs and partially extends to the two side surfaces of the composite foil reserved for welding tabs, and the tab is arranged on the side of the conductive metal layer away from the composite foil; The composite foil comprises an intermediate polymer layer and metal layers respectively arranged on both sides of the intermediate polymer layer; The width of the conductive metal layer extending on the single-side surface of the reserved welding tab foil is 1-5 mm; The thickness of the conductive metal layer is 1-5 μm; The electrical conductivity of the conductive metal layer at room temperature is >10 mS / cm.

2. The composite current collector electrode according to claim 1, characterized in that: The intermediate polymer layer includes any one of PET, PP or PI or a combination of at least two of them.

3. The composite current collector tab according to claim 1, characterized in that: The metal layer independently includes any one of an aluminum layer, a copper layer, a stainless steel layer or a carbon-coated metal layer, or a combination of at least two thereof.

4. The composite current collector tab according to claim 3, characterized in that: The metal layer is independently a carbon-coated metal layer.

5. The composite current collector tab according to claim 4, characterized in that: The thickness of the carbon-coated layer of the carbon-coated metal layer is 0.8-1.2 μm.

6. The composite current collector tab according to claim 1, characterized in that: The thickness of the intermediate polymer layer is 5-8 μm.

7. The composite current collector tab according to claim 1, characterized in that: The single layer thickness of the metal layer is 0.8-1.2 μm.

8. The composite current collector tab according to claim 1, characterized in that: The electrode tab includes an aluminum electrode tab or a copper electrode tab.

9. A method for preparing the composite current collector tab according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) Take the composite foil and reserve the foil for welding tabs at both ends and on the surface of the composite foil; (2) coating a conductive metal paste on the foil at the reserved welding tab, drying it, and welding the tab in a vertical direction at the location coated with the conductive metal paste to obtain the composite current collector tab; The conductive metal paste includes any one of conductive silver paste, conductive aluminum paste, conductive platinum paste, conductive nickel paste, conductive copper paste, conductive tin paste or conductive gold paste, or a combination of at least two thereof; The mass fraction of the conductive metal in the conductive metal paste is 80-90%.

10. The preparation method according to claim 9, characterized in that: The width of the foil reserved for welding the electrode lug in step (1) is 1-2 cm.

11. The preparation method according to claim 9, characterized in that: The length of the foil reserved for welding the electrode ear in step (1) is 1.5-2.5 cm.

12. The preparation method according to claim 9, characterized in that: The viscosity of the conductive metal paste is 150,000-200,000 cps.

13. The preparation method according to claim 9, characterized in that: The average particle size of the metal particles in the conductive metal paste is less than 100 nm.

14. The preparation method according to claim 9, characterized in that: In step (2), the conductive metal paste extends to a width of 1 to 5 mm on both sides of the foil surface at the reserved welding tab along a direction parallel to the current collector.

15. The preparation method according to claim 9, characterized in that: The conductive metal slurry is applied on both sides of the foil material at the reserved welding tab, with a coating length perpendicular to the current collector from the top of the tab to the root being 50-100% of the tab length.

16. The preparation method according to claim 9, characterized in that: The coating method in step (2) includes spraying and / or scraping.

17. The preparation method according to claim 9, characterized in that: The drying temperature is 80~120℃.

18. The preparation method according to claim 9, characterized in that: The drying time is 6 to 24 hours.

19. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite current collector tab according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for welding lithium battery composite current collector tabs

    CN110936010A

  • Battery tab welding structure and preparation method thereof and battery

    CN111435727A